2017
DOI: 10.1590/1807-1929/agriambi.v21n10p681-685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofertilizer obtained by anaerobic digestion of cassava effluent on the development of crambe plants

Abstract: This study aimed to evaluate the effect of applying increasing doses of biofertilizer obtained by the anaerobic digestion of cassava effluent on the development of crambe plants. The experiment was conducted in a protected environment at the Federal University of Paraná (UFPR), Palotina Sector, between April and August 2015. A completely randomized design was used, and five different treatments with the following doses were applied in five replicates: 0, 40, 80, 120, and 160 kg ha-1 of K2O. The following param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…El biofertilizante obtenido por digestión anaeróbica del efluente de la industria de la yuca es una fuente de nutrientes y puede utilizarse como alternativa a los fertilizantes habituales en diversos cultivos como el crambre (Neves et al, 2017), de igual manera como lo observado en la tabla 4, se demuestra que las diferentes fibras estudiadas en la presente investigación después del proceso de la biodigestión contienen macro y micronutrientes con enorme potencial para fertilizante. un efecto superior con 209,00 ppm de Fe, diferenciándose de los otros tratamientos (Tabla 4).…”
Section: Resultados Y Discusiónunclassified
“…El biofertilizante obtenido por digestión anaeróbica del efluente de la industria de la yuca es una fuente de nutrientes y puede utilizarse como alternativa a los fertilizantes habituales en diversos cultivos como el crambre (Neves et al, 2017), de igual manera como lo observado en la tabla 4, se demuestra que las diferentes fibras estudiadas en la presente investigación después del proceso de la biodigestión contienen macro y micronutrientes con enorme potencial para fertilizante. un efecto superior con 209,00 ppm de Fe, diferenciándose de los otros tratamientos (Tabla 4).…”
Section: Resultados Y Discusiónunclassified
“…The methodology for obtaining the biofertiliser differs from those obtained in aerobic digestion [16], in that the method proposed in this study allows the creation of a product directly proportional to its amount of addition.…”
Section: Discussionmentioning
confidence: 99%
“…A biofertiliser obtained by anaerobic digestion of cassava effluent was applied to the development of Crambe plants, the results indicated that the higher the percentage of biofertiliser, the oil values obtained were lower than those of the control, even that the minimum value was achieved with the highest inoculation, in addition to potassium deficiency results in decreased productivity in Crambe grains [16]. Another case is the application of cattle manure biofertiliser to strawberry plants, where it was found that production was greater than 1,250 ml/plant/week in a protected environment and sprayed with cold water and white soil, obtaining the largest fruit size in diameter and length, but with less soluble solids content (Brix) than those grown in the environment in full sun [17].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables are generally sensitive to increased soil electrical conductivity [63]. Salinity is a complex phenomenon that affects the metabolic processes of plants, altering physiological and biochemical parameters [64].…”
Section: Chemical Properties Of Agroindustrial and Heavy Metal Concenmentioning
confidence: 99%